Public Administration: An Islamic Sufi Approach - Bidabad, Bijan (International Journal of Shari'ah and Corporate Governance Research, 2019)
Along with comparing public administration affairs in traditional political, genuinely religious, patrimonial, and charismatic systems, we deal with decision-making problem, and along with mentioning decision-making methods in modern mathematics, the decision making process on the basis of personal value system will be under considerations. If the human beings’ value system moves from caring material affairs towards concerning spiritualties, the consequences of decision-making process would be improved. In establishing management and making hierarchical organization, the more the rate of discipline and ration, the organization framework would become more consolidated. The basic skeleton of an organization includes division of labor, authority, and responsibility, hierarchical relationships of different job categories in the organization, and the qualifications of relationships are of the other items that are being considered in this paper. Mutual understandings and beliefs of members of the organization in approaching organizational goals and their moral commitments to preserve organization's benefits would reduce the costs of supervision and control in organizations including visible and invisible costs, and methods for providing these conditions in Sufism are achieved via purification of the self for every single of the individuals. Meritocracy and favoritism are other discussed topics in this paper. In conclusion, fifty rules for public administration affairs are presented which have been raised by His Excellency Haj Zein ul-Abedin Shirvani, a Sufi Master of two centuries ago.